"An Ongoing Struggle With the Self and Illness": Α Meta-Synthesis of the Studies of the Lived Experience of Severe Mental Illness - Kaite, Charis P.; Karanikola, Maria; Merkouris, Anastasios; Papathanassoglou, Elizabeth (My University, 2015)
The diverse experiences of severely mentally ill persons, most of the times, have not been taken into account, or integrated to the treatment procedures. This meta-synthesis aimed to examine what is like to live with severe mental illness narratives by employing a meta-ethnographic synthesis of seventeen published peer reviewed qualitative studies. Third order analysis revealed as core theme "An ongoing struggle for reconciliation with the self and the illness". Other themes included amongst others: loss of identity, pain of having had one's life stolen, being an outcast. The identification of the importance of the alterations of self-identity throughout the continuum of the severe mental disorder may be the focus of targeted psychosocial interventions.
Keywords: Mental illness; Self-identity